Hypertensive disorders of pregnancy by oocyte donation pregnancy in Japanese women aged 40 years or older: a single-center retrospective cohort study. (2nd January 2021) - Gekka, Yoko; Adachi, Tomoko; Oi, Rie; Nakayama, Setsuko; Kawana, Yukiko; Takeda, Yoshiharu; Nomura, Shuhei; Ozaki, Akihiko; Tanimoto, Tetsuya; Sakamoto, Hideki; Yamashita, Takahiro
ABSTRACT: This study aimed to examine the incidence of hypertensive disorders of pregnancy (HDP) among Japanese women with oocyte donation pregnancy (ODP) aged 40 years or older and estimate whether the women with ODP were more likely to develop HDP than those with autologous oocyte pregnancy (AOP) and spontaneous pregnancy (SP). In our study (N = 1361), the proportions of women who developed HDP were 20.5%, 12.8%, and 7.6% for ODP, AOP, and SP, respectively. After adjustment of covariables, the women with ODP were more likely to develop HDP than those with AOP or SP.